ASSOCIATIONS BETWEEN PRL/RsaI POLYMORPHISM AND SOME PERFORMANCE TRAITS IN HOLSTEIN CATTLE REARED UNDER ORGANIC CONDITION - M. Ozdemir; Z. Sonmez; V. Aksakal (Journal of Animal and Plant Sciences, 2020)
The aim of this study was to ascertain the RsaI polymorphism of the Prolactin (PRL) gene of 186 organically reared Holstein cattle by PCR-RFLP method, in order to reveal the genetic variation of the population, and to reveal the relationship between PRL/RsaI genotypes and some milk yield traits. In the study, the RsaI-/- genotype frequency, RsaI+/+ genotype frequency and RsaI-/+ genotype frequency of Holstein cattle were determined as 0.26, 0.22 and 0.52, respectively. The RsaI- gene frequency was 0.52, and the RsaI+ gene frequency was 0.48. Hardy-Weinberg genetic equilibrium test showed that the distribution of genotype frequencies was determined to be in genetic equilibrium. The relationships between PRL/RsaI polymorphism and the examined milk yield traits were not significant. As a result, an economic and safe method PCR-RFLP for the detection of genetic markers, was successfully used in the determination of the 3 genotypes (RsaI-/-, RsaI-/+, and RsaI+/+) of Prolactin gene in Holstein cattle reared under organic condition, and the results was similar with previously reported literature.
Keywords: Prolactin; PCR-RFLP; polymorphism; marker; cattle